Annual total ocurrence of Kuiseb River flooding from 1962 to 2023 at Gobabeb, Namibia - Yue Li; Eugene Marais; Lixin Wang (PANGAEA, 2025)
The ephemeral Kuiseb River periodically recharges shallow alluvial aquifers, which can provide essential water sources for riparian deep-rooted trees and wildlife (Kaseke et al. (2018, doi:10.4209/aaqr.2017.01.0062)). The annual occurrence days of Kuiseb River flooding at Gobabeb from 1964 to 2019 were collected from Morgan et al. (2021, doi:10.3390/rs13010051).
In: Li, Y et al. (2025): Monthly and annual total of moisture from 1962 to 2023 at Gobabeb, Namibia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.981208